First Detection of West Nile Virus Lineage 2 in Culex pipiens Vectors in Croatia - Goran Vignjević; Nataša Bušić; Nataša Turić; Zsaklin Varga; Brigitta Zana; Ágota Ábrahám; Kornélia Kurucz; Ivana Vrućina; Enrih Merdić (Pathogens, 2024)
The West Nile virus (WNV) has recently become more widespread, posing a threat to both human and animal health. In Western Europe, most outbreaks have been caused by WNV lineage 1, while in Eastern Europe, WNV lineage 2 has led to human and bird mortality. The ability to appropriately manage this threat is dependent on integrated surveillance and early detection. This study aimed to quantify the prevalence of WNV infection in mosquitoes and to identify the circulating viral lineage in eastern Croatia. Mosquito traps were set up in rural and urban areas during the 2021–2023 seasons, and the collected specimens were identified morphologically. Mosquito species Culex pipiens and Aedes albopictus were tested for Flaviviruses using conventional PCR in a heminested system. The positive samples were then subjected to a specific real-time PCR designed to detect WNV. A total of 385 mosquito pools were tested, and positive pools were found in samples from Osijek-Baranja and Vukovar-Srijem, both of which contained Cx. pipiens mosquitoes. Sequencing of amplicons revealed WNV lineage 2 partial NS5 gene sequences. Phylogenetic analysis suggests the Hungarian origin of strain, which complements birds’ migratory routes. These findings indicate the first detection of WNV in mosquitoes in Croatia. This suggests that human cases in this region are likely due to infections with lineage 2 transmitted by local Culex mosquitoes.